2016
DOI: 10.1007/s13691-016-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined large cell neuroendocrine carcinoma and endometrioid carcinoma of the endometrium: a shared gene mutation signature between the two histological components

Abstract: A 61-year-old Japanese woman was diagnosed with FIGO Stage IB endometrioid cancer (EC) combined with large cell neuroendocrine carcinoma (LCNEC). Metastasis to the lymph nodes in the right bronchopulmonary area, mediastinum and brain were also identified. The patient eventually developed pleuritis and pericarditis carcinomatosa, and died of cancer at 51 months after surgery. Because gene aberrations in uterine neuroendocrine carcinoma are still not well understood, we examined alterations in the mutational hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…9 Yasuoka et al 20 found identical clonality between cervical adenocarcinoma and NEC in an X-chromosome clonality assay. Ariura et al 19 also reported identical alterations in PTEN, PIK3CA and FGFR3 in the endocrine and LCNEC components of NEC. Howitt et al 18 reported that 50% of endometrial NECs were ultramutated or hypermutated, which is more representative of other histologic types of endometrial carcinoma than canonical small cell carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…9 Yasuoka et al 20 found identical clonality between cervical adenocarcinoma and NEC in an X-chromosome clonality assay. Ariura et al 19 also reported identical alterations in PTEN, PIK3CA and FGFR3 in the endocrine and LCNEC components of NEC. Howitt et al 18 reported that 50% of endometrial NECs were ultramutated or hypermutated, which is more representative of other histologic types of endometrial carcinoma than canonical small cell carcinoma of the lung.…”
Section: Discussionmentioning
confidence: 80%
“…4 These neoplasms are either "pure" LCNEC or mixed with other histologic components. [5][6][7][9][10][11][12][13][14][15][16][17][18][19] Among other histologic components of endometrial LCNEC, endometrioid carcinoma is the most common histologic type, followed by serous carcinoma. Based on prior reports and our case studies, the most common clinical symptoms are postmenopausal or perimenopausal vaginal bleeding and/or abnormal vaginal discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic profile of endometrial LCNEC is unknown. However, endometrioid carcinoma and endometrial LCNEC share a gene mutation signature with identical alterations in phosphatase and tensin homolog, PIK3CA, and fibroblast growth factor receptor 3, suggesting a common origin[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paraneoplastic syndromes such as Cushing syndrome presenting as fatigue or visual impairment have also been reported. [4][5][6][7][9][10][11][12][13][14]…”
Section: Clinical Presentationmentioning
confidence: 99%
“…High mitotic activity and extensive geographic necrosis are also appreciated. [4][5][6][7][9][10][11][12][13][14] To establish the diagnosis of NEC, a neuroendocrine growth pattern should be present in at least part of the tumor, together with expression of one or more neuroendocrine markers (Chromogranin, Synaptophysin…”
Section: Histopathologic Characteristicsmentioning
confidence: 99%